HISTORICAL PERSPECTIVES ON CARDIOVASCULAR RESEARCH UNDER MICRO-G CONDITIONS - Karl August Kirsch; Hanns-Christian Gunga (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2011)
In this article the early beginnings of space physiology are briefly reported upon based on personal communications and on other reports and publications not currently easily available. Space physiology has evolved from hypergravity experiments. It originally was the aim in centrifuge laboratories to study the limits of g-tolerance. Instead of forward extrapolations from data derived from hypergravity experiments, in 1945-1947 Gauer and Haber extrapolated downwards to zero-g and came to astonishingly precise predictions of what might happen to the human physiology when man entered a zero-g environment. The article under the title "Man under gravity-free conditions" published in German Aviation Medicine World War II Volume 1: 641-644 was the first scientific article laying the basis for further developments in space medicine. This article must be regarded as the beginnings of space physiology. From then on, the manipulation of gravity became a tool for physiologists. In this article, the developments during the pre-war period in Berlin and the USA will be outlined briefly and some of the pioneers in this field mentioned.